Older siblings' influence on sexual behavior of high school adolescents in Mekelle, northern Ethiopia - Haftu M; Berhe H; Tesfay K; Gebremeskel M (Dove Medical Press, 2019)
Mebrahtom Haftu, Haftu Berhe, Kinfe Tesfay, Martha GebremeskelCollege of Health Science, Mekelle University, Mekelle, EthiopiaBackground: Older siblings are one of the key sources of beliefs about sexual activity, including safe sexual practices, and can even exert pressure to engage in sexual activities. This effect persists beyond parental supervision and peer pressure. Despite this, although a considerable body of research has examined parental and peer influence, comparable data on older sibling influence on younger adolescent sexual behaviors are scant, and this area needs in-depth analysis.Objective: The objective of this study was to assess older siblings’ influence on sexual behavior of high school adolescents in Mekelle, northern Ethiopia in 2017–2018.Methods: A cross-sectional study design was used, and a total of 285 adolescents who had ever had sex were sampled randomly from selected schools. Data were entered into Epi-info version 07 and exported to and analyzed with SPSS version 22. Means ± SD, frequency, percentage, and cross-tabulation were used to describe the result. Bivariate and multivariate logistic regression was fitted to compute older sibling influence.Results: Perceiving older sibling sexual behavior as risky increased adolescents’ likelihood of engaging in risky sexual behavior. (AOR 4.52, 95% CI 2.59–7.89) whereas high intimacy with an older sibling (AOR 0.32, 95% CI 0.17–0.59) decreased the odds of risky sexual behavior (AOR 0.59, 95% CI 0.30–0.92).Conclusion: Older siblings had an influence on the sexual behavior of youngr adolescents. Perceiving older sibling sexual behavior as healthy and high sibling intimacy may serve as protective factors; however, risky sexual behavior of an older sibling can increase high school adolescents’ likelihood for same. As such, families should realize that elders can affect their younger siblings’ behavior, included the former in family strategies, and give them responsibility to protect their younger siblings.Keywords: older siblings, influence, adolescent, sexual behaviors, Ethiopia